Islamic Economics Development in Indonesia: Reflection on Contemporary Thoughts of Muslim Intellectuals - Zainal Abidin (Shirkah: Journal of Economics and Business, 2020)
This study aims to establish the record of accomplishment of the strong hallmark of Islamic economic thought and its contribution to economic development. The ideas rooted from the Muslim intellectuals in Indonesia, the scholars of the State Islamic Religious Colleges (PTKIN) as institutions mandated in developing Islamic economics and human resources, were discussed to outline the multifaceted phenomenon of Islamic economic development. This study scrutinizes ideas conveyed in internationally reputed, Sinta 1-indexed, Web of Science-indexed, or Scopus-indexed journals. This study outlined a qualitative approach in the form of library research using content analysis. This study disclosed that Indonesian Muslim intellectuals brought to light the issue of zakah excessing other themes in the Islamic economy as the solution to perennial problems of the social, political, and cultural conditions of Indonesian society. The results of this study contribute to the views of Islamic economic concept and practice as insights and references of its continuous development in Indonesia.